Unveiling the Gaze: Patriarchal Power and Female Resistance in Disgrace - Chen, Xiaoyu; Shi, Chuan (Asia Pacific Economic and Management Review, 2025)
This paper examines the mechanisms of the male gaze in J.M. Coetzee’s Disgrace, situating its female characters within intersecting structures of power, surveillance, and resistance. Drawing on Michel Foucault’s concept of disciplinary power and Jacques Lacan’s theory of the gaze, this study argues that Soraya, Melanie, and Bev Shaw occupy distinct positions within patriarchal visual regimes. Soraya is exoticized and disciplined through an orientalist gaze that renders her a fetishized object; Melanie is ensnared in a web of male desire that simultaneously constructs and erases her agency; and Bev Shaw disrupts the gaze by embracing an aesthetic of desexualized visibility, resisting conventional femininity. Each character, in turn, enacts subversive strategies— withdrawal, silence, and counter-surveillance-that unsettle patriarchal authority. By foregrounding the interplay between gaze, power, and female subjectivity, this paper expands feminist readings of Disgrace, highlighting the novel’s interrogation of gendered oppression and agency in post-apartheid South Africa.